269 Management of cardiac implantable electronic device follow-up in COVID-19 pandemic: lessons learned during Italian lock down. (8th December 2021) - Piro, Agostino; Magnocavallo, Michele; Vetta, Giampaolo; Bernardini, Alessia; Mariani, Marco Valerio; Chimenti, Cristina; Giunta, Giuseppe; Trivigno, Sara; Di Iorio, Martina; Mei, Maria Chiara; Severino, Paolo; Straito, Martina; et al.
Abstract: Aims: Remote monitoring (RM) has significantly transformed the standard of care for patients with cardiac electronic implantable devices. It provides easy access to valuable information, such as arrhythmic events, acute decompensation manifestations, and device‐related issues, without the need of in‐person visits. Methods and results: Starting 1 March, 332 patients were introduced to an RM programme during the Italian lockdown to limit the risk of in‐hospital exposure to severe acute respiratory syndrome‐coronavirus‐2. Patients were categorized into two groups based on the modality of RM delivery [home ( n = 229) vs. office ( n = 103) delivered]. The study aimed at assessing the efficacy of the new follow‐up protocol, assessed as mean RM activation time (AT), and the need for technical support. In addition, patients' acceptance and anxiety status were quantified via the Home Monitoring Acceptance and Satisfaction Questionnaire and the Generalized Anxiety Disorder 7‐item scale. AT time was less than 48 h in 93% of patients and 7% of them required further technical support. Despite a higher number of trans‐telephonic technical support in the home‐delivered RM group, mean AT was similar between groups (1.33 ± 0.83 days in home‐delivered vs. 1.28 ± 0.81 days in office‐delivered patients; P = 0.60). A total of 28 (2.5%) urgent/emergent in‐person examinations were required. A high degree of patient satisfaction was reached in both groups whereas anxiety status was higher in the office‐delivered group. Conclusions: The adoption of RM resulted in high patient satisfaction, regardless of the modality of modem delivery; nonetheless, in‐office modem delivery was associated with a higher prevalence of anxiety symptoms.